Pengaruh Kualitas SDM, Terhadap Kinerja Pegawai dengan Mediasi Budaya Organisasi pada Masa Pandemic Covid 19 Di Dinas PMD Kabupaten Probolinggo - Yossi Eris Kurniawan; Dyah Sawitri; Moch. Saleh (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2021)
The purpose of this study is to test the day of analyzing the quality of human resources has a significant effect on organizational culture, To test the day of analyzing the quality of human resources has a significant effect on employee performance, To test the day of analyzing organizational culture has a significant effect on employee performance, To test today is to analyze resources human resources through organizational culture has a significant effect on employee performance. This research is a quantitative research using quantitative descriptive research. The following documents are available: (i) The quality of human resources has a significant effect on organizational culture. (ii) The quality of human resources has no significant effect on employee performance. (iii) The Organization of the Republic of China reserves the right to cooperate. (iv) The quality of human resources through organizational culture has a significant effect on employee performance.